Impedance Spectroscopy and FTIR Studies of PEG - Based Polymer Electrolytes - Anji Reddy Polu; Ranveer Kumar (E-Journal of Chemistry)
Ionic conductivity of poly(ethylene glycol) (PEG) - ammonium chloride (NH4Cl) based polymer electrolytes can be enhanced by incorporating ceramic filler TiO2 into PEG-NH4Cl matrix. The electrolyte samples were prepared by solution casting technique. FTIR studies indicates that the complex formation between the polymer, salt and ceramic filler. The ionic conductivity was measured using impedance spectroscopy technique. It was observed that the conductivity of the electrolyte varies with TiO2 concentration and temperature. The highest room temperature conductivity of the electrolyte of 7.72×10−6 S cm-1 was obtained at 15% by weight of TiO2 and that without TiO2 filler was found to be 9.58×10−7 S cm−1. The conductivity has been improved by 8 times when the TiO2 filler was introduced into the PEG–NH4Cl electrolyte system. The conductance spectra shows two distinct regions: a dc plateau and a dispersive region. The temperature dependence of the conductivity of the polymer electrolytes seems to obey the VTF relation. The conductivity values of the polymer electrolytes were reported and the results were discussed. The imaginary part of dielectric constant (εi) decreases with increase in frequency in the low frequency region whereas frequency independent behavior is observed in the high frequency region.